The flight of Ringed Teal - Dudley, Noel (Wildfowl, 1957)
After observing the pair of Ringed Teal (Anas leucophrys) which are full-winged and live in the aviary, it has been noticed that, in flight, the wing-beat of the male produces a thin high-pitched whistle. By comparison the female’s wing-beat is almost silent.